PENGARUH CORPORATE GOVERNANCE DAN KEBIJAKAN UTANG TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG LISTING DI BURSA EFEK INDONESIA - Sari, Ati Retna; Setiyowati, Supami Wahyu (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2017)
This Reseach examines the effect of corporate governance and debt policy on financial performance. Debt policy is measured by Debt to Total Asset Ratio and corporate governance in this study using four proxies, namely managerial ownership, institutional ownership, audit committee, and independent board of commissioner. The population in this study is a company listed on the Indonesia Stock Exchange in 2014 until 2015 The research sample set as many as 60 companies in the field of manufacturing. The analysis technique used is multiple linear regression. The results of this study found that debt policy, institutional ownership, audit committee and independent commissioners have an effect on financial performance. Institutional ownership has no effect on financial performance